Habilidades sociales y síndrome de burnout en trabajadores de la subgerencia de serenazgo de la Municipalidad Provincial de Huamanga-Ayacucho, 2021 - Toscano Torres, Miluzka Ivanova (2022)
In the thesis carried out, the objective of determining the relationship of social skills and Burnout syndrome in workers of the serenazgo submanagement of the Provincial Municipality of Huamanga-Ayacucho, 2021 was raised. On the methodology was the type of quantitative research, correlational level and non-experimental cross-sectional design. The population was 109 workers, with a sample of 103 participants and nonprobabilistic sampling through inclusion and exclusion criteria. The technique was survey - questionnaire, the instruments Social Skills Scale (EHS) and Burnout Syndrome Scale (MBI) duly validated and reliable. The statistic that was used to obtain the result of the General Hypothesis was Kendall's Tau_b, obtaining as a p value the result 0.184 which is less than 0.05. Consequently: the (Ho) null hypothesis is accepted and the alternative (Ha) hypothesis is rejected, with a margin of error corresponding to 5% and a confidence level of 95%; allowing to conclude that there is no relationship between social skills and burnout syndrome in workers of the serenazgo sub-management of the Provincial Municipality of Huamanga -Ayacucho, 2021. Keywords: social skills, burnout syndrome